(untitled) (Palestine Technical College Journal for Research and Studies, 2024)
The study aimed to examine the status of school media in public schools in the Gaza Governorates, including its tools, media channels, forms, methods, the level of attention it receives, patterns of interaction with it, the obstacles facing it, and proposed mechanisms for strengthening its presence within the educational environment. The study is classified as a descriptive study that employed the survey method, specifically the survey of practice patterns approach. Data were collected through a questionnaire distributed to a random sample of (204) respondents drawn from the study population, which consisted of (429) school media coordinators working in public schools across the Gaza Governorates. The study concluded that school media coordinators demonstrated a high level of awareness regarding the importance and role of school media, and that their level of engagement in carrying out its activities was also high. School radio ranked as the most frequently used form of school media, with a relative weight of 96.9%, followed by digital media (social networks, platforms, and electronic applications), while media exhibitions ranked last. Facebook was the most widely used media tool among school media coordinators, with a relative weight of 98.4%, followed by school radio, WhatsApp groups, newspapers, bulletins, and printed publications, whereas YouTube ranked last with a low level of use. The study recommended allocating a number of teaching periods to school media coordinators to enable them to effectively follow up and manage media activities without imposing an additional workload on them.